Effect of electronic word-of-mouth (EWOM) message tone on brand attitude. - Goh, Pei Yong. (2011)
Electronic Word of Mouth (EWOM) is communication directed at other consumers about ownership, usage, or characteristics of particular goods and services or their sellers conducted via the Internet. Many researchers have studied the effects of the negative and positive EWOM on consumers’ purchase decision. Past studies on EWOM are based on factors associated with the communicator such as credibility of communicator. Few studies have delved into the significance of message tone on the influence of brand attitude. This paper seeks to find out how the tone of EWOM, coupled with the influence of the valence of the content, impacts readers’ perception of the brand. In this study, two sets of four reviews each differing in terms of valence, product type and tone, were used to test for the effect of tone of EWOM on brand attitude. Responses were compared between those who read the blog with a formal tone with those who read the blog with an informal tone. Results showed that PD is narrower in the case of formal tone than for informal tone review. Respondents who read the formal tone review also had a higher attitude confidence than those who read the informal reviews. Valence also proved to be a significant intervening factor influencing PD perceived by individuals towards the review and attitude confidence of individuals towards the brand. These results will raise marketers’ understanding on the impact of message tone and valence on its brands, empowering marketers with relevant knowledge to leverage on the benefits of EWOM to raise company’s profit. This is important in view of the increasing influence of EWOM due to burgeoning readership.